GRP-054 Drug Safety Profile: Analgesics and Anaesthetics Used in Paediatric Orthopaedics. (12th March 2013) - Falvo, M; Trombetta, L; Luppi, M; Sassoli, V
Abstract : Background: Pharmacological treatment of paediatric patients is a clinical area not deeply investigated because of the health, legal and financial implications. The multidisciplinary team for clinical management of drugs in Rizzoli Orthopedic Institute wanted to meet the clinical demand for standardisation of off-label use. Purpose: To develop a list of safe medicines for use in paediatrics. Materials and Methods: The analysis was conducted considering the data sheets of 169 analgesics and anaesthetic medicines extracted from ATC M-N (60 drugs) and the following sources: TripDataBase, GUF for children 2003, BNF for Children 2011–2012, Who Model Formulary for Children 2010. The information stored in a DB enabled us to classify the medicines as: authorised in paediatrics; licenced with restrictions on use by age/weight/pathology; contraindicated or not recommended in childhood; with no references for use in children. Results: 30 anti-inflammatory/antirheumatic medicines (9 drugs) and 42 analgesics (10 drugs): ibuprofen, paracetamol and pethidine are reference drugs, ketorolac and nimesulide are contraindicated and there is no documentation for age <16 or <12 years; morphine has age limitations, but its use is strongly recommended; 12 muscle relaxants (9 drugs): suxamethonium, vecuronium, atracurium, baclofen, rocuronium are for reference; 31 anaesthetics (14 drugs): bupivacaine, isoflurane, remifentanil, ropivacaine and sevoflurane are authorised, thiopental and ketamine have no indications in childhood but their use is documented; 54 anticonvulsants (18 drugs), gabapentin and pregabalin are contraindicated for neuropathic pain although authorised over 6 years in epilepsy. Conclusions: The results confirmed the limited information contained in the data sheets and the need to apply scientific evidence in paediatrics. Therefore, the resulting list was a tool for clinicians to increase awareness of the off-label use as an aid in the acquisition of informed consent. No conflict of interest.